(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. The country’s entry to international organizations and close cooperation with various foreign partners is a key factor in modernizing and standardizing accounting in the public sector. Public sector institutions are one of the key actors influencing the efficiency and effectiveness of the economy as a whole. Public sector institutions are managed by heads of institutions on the basis of analysis, generalization and systematization of accounting data. That is why there is a link between the public institutions management and accounting. The purpose of the article. The purpose of the article is to study the economic nature of the public sector as one of the economic sectors; to identify the main actors of the public sector through the separation of key identifiers; and to establish a link between the public institutions management and accounting. Results. The article examines and analyzes the economic nature and main characteristics of public sector institutions under different approaches to the formation of the public sector structure; identifies the main subjects of the public sector, which are generalized in two directions according to their functional purpose; summarizes the main characteristics for the identification of the public sector entity, taking into account the Classifier of economic sectors, the system of national accounts, as well as other legal documents; justifies the necessity of division of all public sector subjects into “state enterprises” and “state institutions”; gives the interpretation of the economic nature of “state institution” and “state enterprise”; establishes the relationship and place of accounting in the management of public institutions as public sector entities. Conclusions. The research established that accounting in public sector institutions is branched and dependent on the architecture of the public sector itself. This once again confirms that the economic activity of public sector institutions is reflected in various spheres of economic activity. Issues of accounting in public sector institutions are relevant today given all the transformation processes taking place in the economy.